Pathways to early retirement in Denmark, 1984 - 2000 - Mona Larsen; Peder J. Pedersen (Institute for the Study of Labor (IZA), 2005)
This paper describes and analyses the pathways to early retirement in Denmark. The analyses are based on a 10 per cent panel sample of the population 45-66 years old followed from 1984 onwards. We use a multinomial logit approach to analyse the characteristics of individuals that retire through each pathway compared to those remaining in the labour force. The transition from work to retirement is complex and far from the conventional idea of exit typically occurring from a job at the official pension age. Eight pathways from work to an early retirement program are identified. One group of pathways is transitions directly from employment corresponding to 75 per cent of all transitions in the sample period. The great majority of these transitions occur to an early retirement program. A second group consists of pathways dominated by unemployment insurance benefits (UIB) covering 20 per cent. The remaining 5 per cent of the transitions occur through pathways dominated by benefit programs reflecting a low attachment to the labour force in the period prior to retirement. Overall, availability and/or generosity of retirement programs are important for early retirement through the employment and UIB dominated pathways. For early retirement through other pathways, however, personal characteristics seem to be at least as important as retirement programs.
Keywords: J14; J26; 330; retirement; pathwayas; panel data